Role of Glia-Derived Extracellular Vesicles in Neurodegenerative Diseases - Li, Tianbai; Tan, Xiang; Li, Song; Al-Nusaif, Murad; Le, Weidong (Frontiers in Aging Neuroscience, 2021)
Extracellular vesicles (EVs), as nano-sized vesicles secreted by almost all cells, have been recognized as the essential transmitter for cell-to-cell communication and participating in multiple biological processes. Neurodegenerative diseases (ND), such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis, share common mechanisms of the aggregation and propagation of distinct pathologic proteins among cells in the nervous systems and neuroinflammatory reactions mediated by glia during the pathogenic process. This feature indicates the vital role of crosstalk between neurons and glia in the pathogenesis of ND. In recent years, glia-derived EVs have been investigated as potential mediators of signals between neurons and glia, which provides a new direction and strategy for understanding ND. By a comprehensive summary, it can be concluded that glia-derived EVs have both a beneficial and/or a detrimental effect in the process of ND. Therefore, this review article conveys the role of glia-derived EVs in the pathogenesis of ND and raises current limitations of their potential application in the diagnosis and treatment of ND.